Strip tillage in wheat cultivation: A wind of change in production, greenhouse gas emission and energy use - Md. Nur-e-alam Siddquie; md. Jahedul Islam; mst. Yesmin Abida; md. Monowarul Islam Chowdhury; md. Rashedur Rahman; md. Sajedur Rahman; naznine Khanum (Fundamental and Applied Agriculture)
The experiment was conducted at Paba MLT site, Rajshahi during the year of 2016-17, 2017-18 and 2018-19 in High Ganges River Flood Plain Soil (AEZ-11) to evaluate the performance of Strip tillage (ST) and to estimate the change in input-output energy and GHG emission as compared to Conventional tillage (CT).The production program was done in a compact two hectares' block. Seeding was done in the half of the land with the help of power tiller operated Strip tillage machine and other half by conventional tillage (power tiller) system. The yield was significantly different between ST and CT.The average three years yield was 4264kgha-1 in ST which was 9.6% higher than CT (3892 kgha-1).The strip tillage (ST) emitted 52.3% lower(210 kg CO2eqha-1)greenhouse gas (GHG) in crop residue management sector than CT(440kg CO2eqha-1).The ST liberated 43.3% (170kg CO2eqha-1) lesser GHG in fuel use sector compare to CT (300 kg CO2eqha-1). In case of total emission, ST reduced16.8% total GHG emission (1749kg CO2eqha-1)compare to CT (2099kg CO2eqha-1)during wheat production period. ST liberated 24.1% lower GHG (0.41kg CO2eqkg-1 product) to produce per kilogram product compare to CT (0.54kg CO2eqkg-1 product).The total energy input requirement of wheat was 14.6% lower in ST (16692 MJ ha-1) than CT (19553 MJ ha-1).The total output energy is8.56% higher in ST (164132 MJ ha-1) than CT (151196 MJ ha-1). The energy efficiency or energy ratio in wheat production was found higher in ST (9.83) than CT (7.73). Specific energy was found maximum in CT (5.02 MJ kg-1) as compared to ST (3.92 MJ kg-1). The energy productivity was found 30% higher in ST (0.26 kg MJ-1) than CT (0.20 kg MJ-1). Thus, ST increased grain and energy productivity, reduced GHG emission and utilized lower input energy to produce higher output energy than CT to bring wheat production closer to sustainability in Bangladesh. [Fundam Appl Agric 2024; 9(4.000): 240-246]